2022
DOI: 10.3390/microorganisms10101879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root Zone Aeration on Soil Microbes Species in a Peach Tree Rhizosphere and Root Growth

Abstract: The oxygen content in the root zone considerably affects the growth and development of peach trees. However, few studies have been conducted on the effects of the oxygen content in the root zones of peach trees on soil microbes and root growth. Four-year-old Ruiguang 33/Prunus persica (L.) Batsch trees were used to study the effects of root-zone aeration on soil microbes in a peach orchard, as well as on the soil nutrient contents, peach tree root systems, and plant potassium-to-nitrogen ratios. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Frequent drying-wetting cycles were observed at the treatment outlet during the sampling campaigns, which may have in uenced microbial diversity in the channel bed. Previous studies found that aeration can affect soil microbial communities and increase their diversity [50,51]. However, the impact of aeration on ditch sediment needs further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Frequent drying-wetting cycles were observed at the treatment outlet during the sampling campaigns, which may have in uenced microbial diversity in the channel bed. Previous studies found that aeration can affect soil microbial communities and increase their diversity [50,51]. However, the impact of aeration on ditch sediment needs further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…We also conducted a root diameter classification analysis by selecting a range of root diameters. The results showed that LYGN1 significantly increased the root diameter, resulting in thicker roots, especially in pepper seedlings, which may show a longer lifespan and enhanced function [ 41 ]. All these indicators show the great potential of LYGN1 to promote cucumber and pepper seedling growth and root development.…”
Section: Discussionmentioning
confidence: 99%
“…However, SCA showed high activity in the 20–40 cm soil layer. This may be related to the species and quantity of soil microorganisms in the root zone, soil hydrothermal conditions and root growth secretions ( Sun et al., 2022 ). In addition, the root zone SCA, SPA, SUA and SSA showed higher activity at S1 or S2.…”
Section: Discussionmentioning
confidence: 99%